Pedagogical technology of constructing professional identity of pre-service foreign language teachers - A. A. Palina; G. K. Tleuzhanova; G. B. Sarzhanova (Russian State Vocational Pedagogical University, 2023)
Introduction. The authors of the article investigate the formation of pre-service foreign language teachers' professional identity in the conditions of higher professional education. Its relevance is confirmed by the increased requirements of the society for the personality of a specialist, by the urge for elaborating the internal confidence in his/her professionalism, the ability to build effective professional interactions, and to realise the need for self-expression in his/her profession, all of which are an indicator of high-quality professional training. Aim. The current research aims to provide the scientific justification for the effectiveness of the developed pedagogical technology of constructing the professional identity of students - pre-service foreign language teachers.Methodology and research methods. This study was grounded on the provisions of competency-based, personality-oriented, system-activity, axiological, anthropological approaches; the principles of nature conformity, humanisation, integrity, professional reasonability, activity, and independence; conceptual theoretical provisions of personality and its development in the process of education and professional training, theoretical and practical framework of using modern educational technologies, recent research on professional and pedagogical training of pre-service foreign language teachers and on using innovation technologies in the pedagogical process of vocational training. The study was conducted through the use of the following methods: theoretical analysis of literary sources, generalisation of existing scientific provisions, derivation and systematisation of new knowledge, questionnaire method, observation, experiment, and statistical analysis of the obtained data.Results and scientific novelty. Empirically, the authors have determined and formulated the pedagogical conditions for constructing the professional identity of pre-service foreign language teachers. There has been developed and tested the pedagogical technology that proved its effectiveness in ensuring the formation of students' professional identity till the status of achievement, the development of three components of professional identity (cognitive, emotional, and behavioural), and the correspondent professional and personal qualities and skills.Practical significance. The materials of the study may form the basis for further advances in scientific investigations and bring advantages in psychological coaching during professional evolution of students and experienced foreign language teachers, who need to resolve difficulties associated with professional identity. The developed course on constructing the professional identity of pre-service foreign language teachers can be put into university educational process as part of training methods courses, student teaching placement, tutorial sessions, extracurricular activities on pedagogical excellence, qualification upgrade courses for experienced teachers and educators, methodical seminars, workshops, round tables, as well as into the process of handling the crisis conditions and professional burnout. This course can be included into the university curriculum as a special discipline to prepare teachers both of foreign language and of other school subjects.